Os impactos da logística e da gestão da qualidade sobre o hotel e restaurante cabanas durante a pandemia da Covid-19 - Caldas, Danilo Tourinho (INC - Instituto de Natureza e Cultura (Benjamin Constant), 2022)
The research presented the logistics and quality in the entrepreneurial sector during the COVID19 Pandemic and has as its object of study, The Hotel Restaurante Cabanas, this is located in a place of extreme natural beauty, to which are added the pleasant facilities as well as the hotel and restaurant, not in compliance with this, the company “Cabanas” maintains venues for various events and shows depending on the client to be hired, highlighting its quality service according to its visitors-clients or users who started to use the services provided or offered by the company Cabanas. The enterprise that has been in existence for several years is the result of a lot of effort, it differs from any other enterprise, as it indirectly generates revenue for municipality, as it promotes local, national and international tourism. Logistics and quality of the project in question. In the object of study, logistics are appraised some modals as will be explained in the development of the research, while the existing quality of the enterprise was measured through the likert school. It is worth mentioning that the company maintains its own and autonomous logistics, in its various activities in the various areas in which the company operates. The methodology that was approached was the field research, considering the spontaneous observation of the facts, supported by exploraty research. The results obtained point to a quality service in some item at the Cabanas Restaurant, in addition to the description of the logistics use in a clear and precise manner.